Audyt wewnętrzny jako mechanizm ładu organizacyjnego w szkolnictwie wyższym - Grzegorz Palus (Studia i Materiały)
Purpose: The primary objective of the study is to verify the use of the internal audit function as an instrument of New Public Management (NPM) and a mechanism for improving the activities of Polish universities.